Total versus partial adrenalectomy in bilateral pheochromocytoma – a systematic review and meta-analysis - Zawadzka, Karolina; Tylec, Piotr; Małczak, Piotr; Major, Piotr; Pędziwiatr, Michał; Pisarska-Adamczyk, Magdalena (Frontiers in Endocrinology, 2023)
Background: Although in patients with bilateral pheochromocytoma, partial adrenalectomy is the only way to avoid the need for lifelong steroid supplementation, the risk of tumor recurrence raises questions about this procedure. Our study aimed to compare patients with bilateral pheochromocytoma undergoing partial versus total adrenalectomy through a systematic review with meta-analysis. Methods: A systematic search was carried out using databases (MEDLINE, EMBASE, Scopus, Web of Science, CENTRAL) and registers of clinical trials (ClinicalTrials.gov, European Trials Register, WHO International Trials Registry Platform). This meta-analysis included studies up to July 2022 without language restrictions. A random effects model meta-analysis was performed to assess the risk of tumor recurrence, steroid dependence and morbidity in patients with bilateral pheochromocytoma undergoing total versus partial adrenalectomy. Results: Twenty-five studies were included in the analysis involving 1444 patients. One in three patients after partial adrenalectomy required steroid supplementation during follow-up: RR 0.32, 95% CI: 0.26-0.38, P < 0.00001, I2=21%. Patients undergoing partial adrenalectomy had a lower risk of developing acute adrenal crisis: OR 0.3, 95% CI: 0.1-0.91, P=0.03, I2=0%. Partial adrenalectomy was associated with a higher risk of recurrence than total adrenalectomy: OR 3.72, 95% CI: 1.54-8.96, P=0.003, I2=28%. Conclusion: Partial adrenalectomy for bilateral pheochromocytoma is a treatment that offers a chance of preserving adrenal hormonal function, but is associated with a higher risk of local tumor recurrence. Patients with bilateral pheochromocytoma after partial adrenalectomy did not have higher rates of metastasis or mortality than those after total adrenalectomy.